2021
DOI: 10.1111/jen.12961
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the efficacy of attracticidal spheres for management of Drosophila suzukii (Diptera Drosophilidae)

Abstract: Spotted‐wing drosophila, Drosophila suzukii Matsumura, is an invasive pest in the United States, Europe and South America. Females are able to oviposit in intact soft‐skinned fruit, resulting in significant economic losses due to larval feeding. Attracticidal spheres, originally developed for the apple maggot, Rhagoletis pomonella Walsh, have been used as a management tool for D. suzukii in a few studies, but little is known about their longevity as a killing device and their performance under varying pest den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…When the fly pressure is too high, however, HOOK SWD becomes less effective at controlling D. suzukii , which has been observed for other semiochemical control approaches targeting insect pests such as mating disruption (Barclay & Judd, 1995) when the suppressive effect of the sex pheromone treatment is competitive or population‐density dependent (Miller et al, 2006). For instance, comparable results were observed in similar semi‐field cage studies with attracticidal spheres where high relative densities of D. suzukii flies resulted in greater emergence of adult flies from raspberry and blueberry fruit than at moderate or low relative densities (Nixon et al, 2022).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…When the fly pressure is too high, however, HOOK SWD becomes less effective at controlling D. suzukii , which has been observed for other semiochemical control approaches targeting insect pests such as mating disruption (Barclay & Judd, 1995) when the suppressive effect of the sex pheromone treatment is competitive or population‐density dependent (Miller et al, 2006). For instance, comparable results were observed in similar semi‐field cage studies with attracticidal spheres where high relative densities of D. suzukii flies resulted in greater emergence of adult flies from raspberry and blueberry fruit than at moderate or low relative densities (Nixon et al, 2022).…”
Section: Discussionsupporting
confidence: 58%
“…Particularly, one of these strategies that have gained the most attention is attract‐and‐kill, a strategy that combines an attractive stimulus either visual or chemical (e.g., fruit, yeast or other related odours), phagostimulants (e.g., sugars) and a killing agent (e.g., an insecticide) (Cloonan et al, 2018). For example, red attracticidal spheres, that combine a phagostimulant (e.g., sugar), a visual stimulus (e.g., red colour) and an insecticide, can reduce D. suzukii infestation in raspberry and blueberry (Nixon et al, 2022; Rice et al, 2017). In a recent study, Rehermann et al (2022) showed that the yeast Hanseniaspora uvarum (Niehaus), the predominant yeast species found in the midgut of D. suzukii larvae and adults and known to attract the adults (Hamby et al, 2016; Knight et al, 2016; Mori et al, 2017), can be combined with the insecticide spinosad as an attract‐and‐kill formulation to reduce fruit infestation and insecticide residues on the fruit.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of blue dye to a sucrose and yeast extract preparation did not affect feeding of D. melanogaster in a laboratory assay (Deshpande et al, 2014). For D. suzukii, the use of red plastic spheres with an impregnated wax, sucrose and spinetoram cap contributed to pest control in raspberry and blueberry crops (Nixon et al, 2021). On a note of caution, we cannot discount the possible effect of social facilitation in these results as both sexes of D. suzukii F I G U R E 4 Mean (± SE) percentage of mortality of female flies offered 25 ppm spinosad in a 4% mixture (sucrose + HFCS + glycerol) alone, or in combination with apple juice (1%-10%), under non-choice conditions.…”
Section: Discussionmentioning
confidence: 93%
“…For D . suzukii , the use of red plastic spheres with an impregnated wax, sucrose and spinetoram cap contributed to pest control in raspberry and blueberry crops (Nixon et al., 2021). On a note of caution, we cannot discount the possible effect of social facilitation in these results as both sexes of D .…”
Section: Discussionmentioning
confidence: 99%